METHODS OF EQUALIZATION AND EVALUATION OF GEODESIC BASES - Kasimov Mahmud (Western European Studies, 2024)
In this article, equalization and evaluation of geodesic bases is important to ensure accuracy and reliability in geodesic studies. This article details methods for equalizing and evaluating geodesic bases. These methods help to accurately match the measurements of points in geodesic networks and assess their degree of accuracy.
Keywords: geodesic bases; equalization methods; evaluation methods